Insulin versus Lipid Emulsion in a Rabbit Model of Severe Propranolol Toxicity: A Pilot Study. (17th February 2011) - Harvey, Martyn; Cave, Grant; Lahner, Daniel; Desmet, Jan; Prince, Gaynor; Hopgood, Gary
Abstract : Background and objective . Beta-blocker overdose may result in intractable cardiovascular collapse despite conventional antidotal treatments. High dose insulin/glucose (ING), and more recently intravenous lipid emulsion (ILE), have been proposed as potentially beneficial therapies in beta blocker intoxication. We compare efficacy of the novel antidotes ING, with ILE, in a rabbit model of combined enteric/intravenous propranolol toxicity. Methods . Sedated, mechanically ventilated and invasively monitored New Zealand White rabbits underwent mini-laparotomy and enterostomy formation with 40 mg/kg propranolol instilled into the proximal small bowel. At 30 minutes propranolol infusion was commenced at 4 mg/kg/hr and continued to a target mean arterial pressure (MAP) of 50% baseline MAP. Animals were resuscitated with insulin at 3 U/kg plus 0.5 g/kg glucose (ING group), or 10 mL/kg 20% Intralipid (ILE group). Results . Rate pressure product (RPP; RPP = heart rate × mean arterial pressure) was greatest in the ING group at 60 minutes (P < . 05 ). A trend toward greater heart rate was observed in the ING group (P = . 06 ). No difference was observed in survival between groups (4/5 ING versus 2/5 ILE;P = . 524 ). Conclusions . High dose insulin resulted in greater rate pressure product compared with lipid emulsion in this rabbit model of severe enteric/intravenous propranolol toxicity.